Polyphiloprogenitive: T.S. Eliot's Notion of Culture - Brlek, Tomislav (2003)
In his various writings on the subject, T.S. Eliot develops the notion of culture as a comprehensive and highly complex system of meaning production, wherein social, political and other contexts are constitutive of experience formation, while the experiences thus formed are what the cultural system consist of. The multiform dialectical interaction that is culture crucially involves the notion of community and postulates ongoing interpretation as the lifeline of all cultural activity, predicated as it is on the ceaseless semiotic feedback between the heterogeneous codes that comprise it and the communicative exchange with the "outside" through which its "inside" is actually brought about. Such considerations closely link Eliot's understanding of culture with Lotman's concept of the semiosphere.